“Assessment of Infectious Diseases and Clinical Microbiology Clinics in Turkey: Variations Among Clinics and Curriculum Adherence” - Eren Öztürk; Elif Agüloğlu Bali; Taliha karakök; Melike Törüyenler Coşkunpınar; Merve Buyukkoruk (Journal of Global Antimicrobial Resistance)
AIM/BACKGROUND: Specialty education in our country follows core curricula within the ‘Regulation on Speciality Education in Medicine and Dentistry’. Despite this, differences exist between clinics. Assessing these differences was necessary to standardize education and raise awareness. METHODS: A total of 100 individuals from 87 clinics in Turkey, competent in infectious diseases and clinical microbiology (IDCM), were surveyed using a 52-item online questionnaire. The data from each respondent were compared within their respective centers. RESULTS: The mean age of participants was 29.52 years, with a majority being female (71%). The mean number of faculty members per training clinic was 4.45 (range 1-13), and the mean number of residents was 13.19. Although one-third of faculty presence is recommended, this ratio was less than one-third in 40% of clinics. In outpatient clinics, 75% of residents were not accompanied by a lecturer, though a lecturer was accessible (97%). The mean number of computers in resident rooms was 2.82 (range 0-7), with 53% of residents waiting for a computer. About half of the teaching clinics lacked a microbiology laboratory.A significant difference was observed between hospital types regarding faculty members acting as narrators (63%), more pronounced in university and research hospitals (Table 1). The most common procedure was lumbar puncture (100%), and the least common was joint fluid sampling (7%). Annual or semi-annual assessments occurred in 90% of clinics. CONCLUSIONS: Discrepancies exist between clinics' facilities and the IDCM curriculum. Standardizing education requires adequate facilities and enough qualified staff.